The Uncanny: beyond Freud - Achón Lezaun, Irene (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
Our purpose, with this monograph of Tropelías, is to fathom into the term ‘sinister’ and investigate, a little more, why we continue to get closer to what causes it, why it attracts our attention and what moves in us. What do we hope to find and also what do we intend to hide, what do we intend to enclose when, voluntarily, we submit to its effects: how does the sinister help us?, does it, in some way, vent our dark part?